2013
DOI: 10.14214/sf.935
|View full text |Cite
|
Sign up to set email alerts
|

Tree biomass and soil carbon stocks in indigenous forests in comparison to plantations of exotic species in the Taita Hills of Kenya

Abstract: Carbon (C) densities of the tree biomass and soil (0-50 cm) in indigenous forest and plantations of eucalyptus, cypress and pine in the Taita Hills, Kenya were determined and compared. The cypress and pine plantations were about 30-years-old and eucalyptus plantations about 50-years-old. Biomass C densities were estimated from breast height diameter and wood density using allometric functions developed for tropical species and an assumed C content of 50%. Belowground biomass C densities were estimated using ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
25
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 55 publications
7
25
0
2
Order By: Relevance
“…There are few studies which have been conducted to examine the carbon storage potential of three main forest fragments; Mbololo, Ngangao and Chawia in Taita Hills (Omoro et al, 2013). The calculation of carbon stock held by individual trees has been done using wood density values for the indigenous species obtained from Reyes et al (1992) and the global wood density database developed by Zanne et al (2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few studies which have been conducted to examine the carbon storage potential of three main forest fragments; Mbololo, Ngangao and Chawia in Taita Hills (Omoro et al, 2013). The calculation of carbon stock held by individual trees has been done using wood density values for the indigenous species obtained from Reyes et al (1992) and the global wood density database developed by Zanne et al (2009).…”
Section: Introductionmentioning
confidence: 99%
“…Inclusion of height and wood density in above-ground biomass (AGB) estimation models has been found to improve on the accuracy in quantifying the carbon stock (Chave et al, 2005(Chave et al, , 2014. However, to-date, studies conducted in fragmented forests of Taita Hills to quantify carbon sequestration potential of the forest fragments have used models with diameter at breast height (DBH) and wood density to estimate the amount of carbon held by these forests (Omoro et al, 2013) leaving out tree height; an important variable in biomass estimation. Improving on the accuracy in quantifying the carbon stock by using models for estimating AGB that integrate diameter at breast height (DBH), wood density and height to calculate the carbon stored by the Mbololo, Ngangao and Chawia forest fragments is therefore a prerequisite in tackling climate change in the context of REDD+ activities (reducing emissions from deforestation and forest degradation and increasing the carbon stock in forests), where governments require more accurate assessment of the forest carbon stocks.…”
Section: Introductionmentioning
confidence: 99%
“…El número de árboles, el área basal y la biomasa aérea, presentaron valores similares a los registrados en otros bosques tropicales de montaña donde se reportan rangos de 476-879 árboles por hectárea; 35.4-46.5m 2 /ha de área basal y 94-409Mg/ha de biomasa aérea (Cumsee et al, 2010;Girardin et al, 2010;Moser et al, 2011;Álvarez, García, Krasilnikov, & García, 2013). No obstante, los resultados obtenidos en este estudio, son más próximos a los registrados en bosques tropicales de tierras bajas en Borneo (457.10Mg/ha; Slik et al, 2010), Uganda (603.90Mg/ha; Lewis et al, 2013), y Kenia (607Mg/ha; Omoro, Starr, & Pellikka, 2013); y casi dos veces superior al promedio reportado para la Amazonía (288.60Mg/ha; Malhi et al, 2006) y al promedio pantropical recientemente reportado por Spracklen & Righelato (2013) de 257.10Mg/ha.…”
Section: Fig 1 (A)unclassified
“…However the amount of biomass and carbon on site is largely determined by human activities and management mechanisms. [5] [6] showed that tree biomass and soil carbon densities in indigenous forests were not consistently greater than in plantations of exotics, depending on the plantations age and species. Although Meta analysis studies have shown that replacing native forests with agriculture and plantations (when less than 40 years of age) generally reduces soil carbon stock [7] [8] [9].…”
Section: Introductionmentioning
confidence: 99%
“…Global instruments to reward countries embarking on reduced deforestation and degradation (REDD) and application of sustainable management of forest services (REDD+) to enhance carbon sequestration recognize the significance of indigenous tropical forest trees in carbon emissions sequestration capacity and mitigation of climate change [5] [6]. However the amount of biomass and carbon on site is largely determined by human activities and management mechanisms.…”
Section: Introductionmentioning
confidence: 99%